ANALISIS KETERSEDIAAN DAN KEBUTUHAN AIR UNTUK IRIGASI PASANG SURUT DESA KARANG BARU KECAMATAN SUMBER MARGA TELANG - Sarkoni; Permatasari, Rosmalinda; Andayani, Reni; Marlina, Ayu (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2024)
Area is located in Karang Baru Village with an area of 2,100 ha. The Tidal Irrigation Channel is used to irrigate rice fields in Karang Baru Village. The source of irrigation water comes from the Musi River which has an impact on sea tides. The aim of this research is to determine the availability of water for tidal irrigation in Karang Baru Village, to determine the need for tidal irrigation water according to irrigation planting patterns. Primary data is data taken in the form of planting pattern data and the type of rice used, secondary data is rainfall data and climatology data. Evapotranspiration calculations use the Penman method and water availability calculations use F.J. Mock. After calculating water availability for tidal irrigation in Karang Baru Village using the F.J Mock method, the largest value occurred in March at 0.89 m3/second, while the smallest value occurred in July at 0.01 m3/second. The need for tidal irrigation water in Karang Baru Village during land preparation, the maximum water need occurs in October at 0.0061 m3/second, for water layer changes the maximum occurs in November at 0.0041 m3/second.